Patogenos del suelo en el cultivo de pimenton en la zona baja del municipio Jimenez, Estado Lara, Venezuela - Escalona, Y.=700 1 Rodriguez, D.; Contreras, N.; Jimenez, N.
(Es, En)
ilus., 26 ref.
Keywords: ORGANISMOS PATOGENOS; SUELO; CAPSICUM ANNUUM; RHIZOCTONIA; ERWINIA; RALSTONIA; FUSARIUM; MELOYDOGINE; DIAGNOSTICO; VENEZUELA